Synthesis and biological evaluation of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives via click chemistry approach - Kategaonkar, Amol H.; Shinde, Pravin V.; Kategaonkar, Atul H.; Pasale, Sharad K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (European Journal of Medicinal Chemistry, 2010)
Synthesis of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives (4a-h) using 1,3-dipolar cycloaddition (click chemistry) reaction of 3-(azidomethyl)-2-chloro-quinoline derivatives (3a-h) with phenyl acetylene in the presence of Cu(I) catalyst has been achieved in very high yield. These molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 2; 2-Chloro3-formyl quinoline; 3-Triazole; Antibacterial; antifungal; Click chemistry

Synthesis and characterization of polyamides containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Wadgaonkar, Prakash P. (European Polymer Journal, 2010)
A new aromatic diacid monomer viz., 4-(4'-carboxyphenoxy)-2-pentadecylbenzoic acid was synthesized starting from cardanol and was characterized by FTIR, (1)H- and (13)C NMR spectroscopy. A series of new aromatic polyamides containing ether linkages and pendant pentadecyl chains was prepared by phosphorylation polycondensation of 4-(4'-carboxyphenoxy)-2-pentadecylbenzoic acid with five commercially available aromatic diamines viz., 1,4-phenylenediamine, 4,4'-oxydianiline, 4,4'-methylenedianiline, 1,3-phenylenediamine, and 4,4'-(hexafluoroisopropylidene)dianiline. Inherent viscosities of the polyamides were in the range 0.45-0.66 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C. The introduction of ether linkages and pendant pentadecyl chains into polyamides led to an enhanced solubility in N,N-dimethylacetamide and 1-methyl-2-pyrrolidinone at room temperature or upon heating. The polyamides could be solution-cast into tough, flexible and transparent films from their N,N-dimethylacetamide solution. Wide angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were essentially amorphous in nature. X-Ray diffractograms also displayed a diffuse to sharp reflection in the small-angle region (20 = similar to 2-5 degrees) for the polyamides characteristics of formation of loosely to well-developed layered structure arising from packing of flexible pentadecyl chains. The glass transition temperature observed for the polyamides was in range 139-189 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of the polyamides was in the range 425-453 degrees C indicating their good thermal stability. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: alkyl side-chain; Cardanol; Cashew nut shell liquid; Pentadecyl chains; polyamides

Poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing cardo decahydronaphthalene groups: synthesis and characterization - Honkhambe, Pandurang N.; Pasale, Sharad K.; Bhairamadgi, Nagendra S.; Kumbhar, Kishor P.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
New poly(ether ether ketone)s and poly (ether ether ketone ketone) s were synthesized by polycondensation of each of the three bisphenols, viz., 4,4'-(octahydro-2(1H)-naphthylidene) bisphenol, 4,4'-(octa-hydro-2(1H)-naphthylidene) bis-3-methylphenol, and 4,4'(octahydro-2(1H)-naphthylidene) bis-3,5-dimethylphenol with 4,4'-difluorobenzophenone and 1,3-bis(4-fluorobenzoyl) benzene in a mixture of N,N-dimethylacetamide and toluene [1 : 1 (v/v)] in the presence of anhydrous potassium carbonate. Inherent viscosities of poly(ether ether ketone) s and poly (ether ether ketone ketone) s were in the range 0.32-0.80 dL/g and number-average molecular weights were in the range 16,100-55,900 g/mol. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, and 1-methyl-2-pyrrolidinone at room temperature and could be cast into tough, transparent, and flexible films from their chloroform solutions. Wide angle x-ray diffraction measurements revealed the amorphous nature of poly(ether ether ketone) s and poly (ether ether ketone ketone) s. The glass transition temperature poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 185-251 degrees C. The temperature at 10% weight loss, determined from thermogravimetric analysis, of poly(ether ether ketone) s and poly(ether ether ketone ketone) s in nitrogen atmosphere was in the range 462-493 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1607-1613, 2011
Keywords: bisphenol; cardo decahydronaphthalene; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Synthesis and characterization of organo-soluble poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Honkhambe, Pandurang N.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
Poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant pentadecyl chains were synthesized by polycondensation of each of the two bisphenol monomers viz, 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl] ethane and 1,1-bis(4-hydroxyphenyl)-3-pentadecyl cyclohexane with activated aromatic dihalides namely, 4,4'-difluorobenzophenone, and 1,3-bis(4-fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene, in the presence of anhydrous potassium carbonate. Polymers were isolated as white fibrous materials with inherent viscosities and number average molecular weights in the range 0.70-1.27 dL g(-1) and 76,620-1,36,720, respectively. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were found to be soluble at room temperature in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, and pyridine and could be cast into tough, transparent, and flexible films from their solutions in chloroform. Wide angle X-ray diffraction patterns exhibited a broad halo at around 2 theta = similar to 19 degrees indicating that the polymers containing pentadecyl chains were amorphous in nature. In the small-angle region, diffuse reflections of a typically layered structures resulting from the packing of pentadecyl side chains were observed. The temperature at 10% weight loss, obtained from TG curves, for poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 416-459 degrees C, indicating their good thermal stability. A substantial drop in glass transition temperatures (68-78 degrees C) was observed for poly(ether ether ketone) s and poly(ether ether ketone ketone) s due to ``internal plasticization'' effect of flexible pendant pentadecyl chains. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 3689-3695, 2011
Keywords: alkyl side-chain; Cashew nut shell liquid; CNSL; pentadecyl; poly(arylene ether)s; poly(ether ketone)s; polyethers; renewable